2022
DOI: 10.3390/healthcare10061136
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diagnostic Imaging Sector in Public Hospitals in Northern Jordan

Abstract: The most effective diagnostic methods in the medical field are diagnostic imaging techniques such as radiography, computed tomography (CT), magnetic resonance imaging (MRI), and nuclear medicine, which are used to visualize internal body to diagnose it, determine potential treatment, and evaluate and forecast care results. Therefore, the purpose of this research is to assess the diagnostic imaging sector, at three major public hospitals in the northern part of Jordan, according to regional and global requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Numerous other studies conducted in Europe and Africa found that the pandemic posed significant challenges to radiographers’ professional practice in a variety of ways [ 1 , 5 , 6 , 10 , 11 , 12 , 13 , 14 ]. A study conducted in Jordan presented the results distribution obtained from a computed tomography (CT) scanner and magnetic resonance imaging (MRI) units in some countries /per million population, concluding that in some countries, such as Jordan, the amount of diagnostic imaging equipment does not correlate with the population number, which leads to an overload of work in many of radiology units [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other studies conducted in Europe and Africa found that the pandemic posed significant challenges to radiographers’ professional practice in a variety of ways [ 1 , 5 , 6 , 10 , 11 , 12 , 13 , 14 ]. A study conducted in Jordan presented the results distribution obtained from a computed tomography (CT) scanner and magnetic resonance imaging (MRI) units in some countries /per million population, concluding that in some countries, such as Jordan, the amount of diagnostic imaging equipment does not correlate with the population number, which leads to an overload of work in many of radiology units [ 15 ].…”
Section: Introductionmentioning
confidence: 99%